2018
DOI: 10.1111/1744-7941.12179
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance work systems as a remedy for growing pains: evidence from South Korean organizations

Abstract: Drawing on literatures from a contingency perspective of strategic human resource management and a dynamic resource-based view, this study examines dynamic patterns of investment in highperformance work systems (HPWS) to support labor productivity of growing organizations. We analyzed a four-wave panel dataset from 267 establishments in South Korea and found that higher usage of HPWS at a prior point in time and increasing usage of HPWS over time led to consistently improved labor productivity when the employm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Indeed, Asia Pacific Journal of Human Resources (e.g. Kim et al , 2018; Rhee et al , 2018) and The International Journal of Human Resource Management (e.g. Choi and Yoon, 2015; Horak, 2017; Shin et al , 2018) published the majority of the identified Korea-based studies (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Asia Pacific Journal of Human Resources (e.g. Kim et al , 2018; Rhee et al , 2018) and The International Journal of Human Resource Management (e.g. Choi and Yoon, 2015; Horak, 2017; Shin et al , 2018) published the majority of the identified Korea-based studies (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ubeda-Garcia et al , 2017), on employees' performance and productivity (e.g. Cooper et al , 2019; Han et al , 2017; Kim et al , 2018), as well as on the creation of positive employee well-being effects (e.g. Ananthram et al , 2018; Tremblay, 2019; Veld and Alfes, 2017).…”
Section: Theory and Conceptual Frameworkmentioning
confidence: 99%
“…As far as the past two years are concerned, HPWS still lies at the forefront of the Human Resource Management (HRM) literature (e.g. Brinck et al , 2019; Han et al , 2017; Kim et al , 2018; Messersmith et al , 2018). Overall, most recent research has shifted to the positive contribution of HPWS towards employee attitudes and behaviors, and well-being (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As organizations grow, they seek internal methods and structures to tackle growth pains such as communication problems, coordination problems, disengaged employees, or the loss of informality (DeSantola & Gulati, 2017). HRM systems such as high-performance work systems have been proposed as a solution to these issues (Kim, Kim, Kim, Han, & Lepak, 2018). However, we know little about how, when and why entrepreneurs implement such HRM systems.…”
Section: Future Research At the Firm Levelmentioning
confidence: 99%